CRM jako instrument zarządzania wiedzą o klientach na przykładzie banku - Teneta-Skwiercz, Dorota; Matulko, Marta (CRM as a tool of client knowledge management on the bank example, 2007)
The main intention of this article may be found in presenting the most effective and influential way of CRM as a tool of goveming human’s relationships in bank. Apart from short but deep description of CRM and three of its subsystems, such as: analytical CRM, operative CRM, and as a basis of an organizational knowledge - the article presents how all mentioned subsystems may function within the bank.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Zarządzanie (5); 2007; nr 1187, s. 275-283